Analysis of the Vibro-Acoustic Behavior of a Stiffened Double Panel-Cavity System. (11th July 2022) - Wang, Na; Chen, Mingfei; Zhang, Yantao; Shi, Shuangxia; Jin, Guoyong; Liu, Zhigang
Abstract : An analytical solution for the vibro-acoustic behavior analysis of a stiffened double panel-cavity coupled system is presented. Unlike existing methods, this method is flexible with parameter analysis and can simulate the elastic boundary conditions of a stiffened double panel structure. The displacements of the stiffened double panel structures and the sound pressure of two inner acoustic cavities are expressed by two-dimensional (2D) and three-dimensional (3D) improved Fourier series methods, respectively. Then, the unknown coefficients of the vibro-acoustic control equation are solved by the Rayleigh–Ritz method based on the virtual works principle applied to the coupled system. In numerical results, the accuracy and effectiveness of the proposed method are validated by several comparison examples. Finally, the influence of some parameters on the vibro-acoustic behavior of the coupled system is investigated. Numerical results show that the external acoustic excitation at a certain angle can stimulate more resonant responses of the panel-cavity coupled system. This work can predict quickly the vibro-acoustic behavior of the stiffened double panel-cavity coupled system with a small truncation number. Some new results can be used as reference data for future work.